Antenatal Corticosteroid Therapy Attenuates Angiogenesis Through Inhibiting Osteoclastogenesis in Young Mice - Chai, Yu; Su, Jianwen; Hong, Weisheng; Zhu, Runjiu; Cheng, Caiyu; Wang, Lei; Zhang, Xianrong; Yu, Bin (Frontiers in Cell and Developmental Biology, 2020)
Antenatal corticosteroid therapy (ACT) has been shown to reduce morbidity and mortality rates in preterm delivery, but the fetal is more likely to face the risk of low bone mineralization and low fetal linear growth. However, the mechanism of PDE induces low bone mineralization remains largely unknown. Preosteoclasts (POC), which play an important role in angiogenesis and osteogenesis, are specifically regulating Type H vessels (CD31hiEmcnhi) vessels formation by secreting platelet-derived growth factor-BB (PDGF-BB). We find that the number of preosteoclasts and POC-secreted PDGF-BB is dramatically decreased in PDE mice, contributing to the reduction in type H vessels and bone mineralization during the mouse offspring. Quantitative analyses of μCT show that the ACT mice have a significant reduction in the mass of trabecular bone relative to the control group. Mononuclear preosteoclasts in trabecular bone decreased in ACT mice, which leads to the amount of PDGF-BB reduced and attenuates type H vessel formation. After sorting the Rank+ osteoclast precursors using flow cytometry, we show that the enhancer of zeste homologue 2 (Ezh2) expression is decreased in Rank+ osteoclast precursors in PDE mice. Consistent with the flow data, by using small molecule Ezh2 inhibitor GSK126, we prove that Ezh2 is required for osteoclast differentiation. Downregulate the expression of Ezh2 in osteoclast precursors would reduce PDGF-BB production. Conditioned medium from osteoclast precursors cultures treated with GSK126 inhibited endothelial tube formation, whereas conditioned medium from the vehicle group stimulated endothelial tube formation. These results indicate ezh2 expression in PDE osteoclast precursors is suppressed, which attenuates the preosteoclast number and PDGF-BB secretion, thus inhibiting type H vessel formation and ACT associated low bone mineralization.